Prescribing and administration of opioid analgesics in residents of aged care facilities - Areej Numan Hussein; Lynne Emmerton (Wolters Kluwer Medknow Publications, 2019)
Objective: Optimal pain management in residents requires an understanding of prescribing and administration of opioid analgesics. This study aimed to describe opioid administration for elderly residents in a selection of aged care facilities. Methods: A cross-sectional audit of analgesics administration was conducted for all 458 residents of three-aged care facilities on May 1, 2017. The facilities (each ~160 beds) represented a geographically diverse area in Perth, Australia, and varying service levels by nurse practitioners. Data were accessed using the iCare® platform and transcribed into a customized database. Data were reported descriptively, with relationships between categorical variables examined using the Chi-square analysis. Main outcome measures in the study were the prevalence of administration of opioids compared to that of nonopioid analgesics and no analgesics on the audit date, and characteristics of the opioid prescriptions (the type of prescriber and nursing/care staff involved in the dose administration). Findings: Of 458 residents, 95 (20.7%) received an opioid analgesic on the audit date; 231 had also received a nonopioid analgesic. The most common opioid (34 residents) was a brand of oxycodone hydrochloride and naloxone hydrochloride as 10/5 mg tablets. There was no significant tendency for opioid prescribing by classification of the prescriber, nor for any category of nursing/care staff to administer the particular types of analgesics. Conclusion: The tendency for prescribing of opioids showed no significant among the prescribers. Finally, the administration of opioids was predominantly by caregivers. This represents the first step in a program of activity to ensure the quality use of potent analgesics in an aged care provider network.